Thermal degradation, visco-elastic and fire-retardant behavior of hybrid Cyrtostachys Renda/kenaf fiber-reinforced MWCNT-modified phenolic composites - Loganathan, Tamil Moli; Sultan, Mohamed Thariq Hameed; Ahsan, Qumrul; Jawaid, Mohammad; Naveen, Jesuarockiam; Md Shah, Ain Umaira; Abu Talib, Abd. Rahim; Basri, Adi Azriff (Springer, 2022)
Natural fibers have emerged as a potential alternate to synthetic fibers, because of their excellent performance, biodegradability, renewability and sustainability. This research has focused on investigating the thermal, visco-elastic and fire-retardant properties of different hybrid Cytostachys Renda (CR)/kenaf fiber (K) (50/0; 35/ 15, 25/25, 15/ 35, 0/50)-reinforced MWCNT (multi-walled carbon nanotubes)-modified phenolic composites. The mass% of MWCNT-modified phenolic resin was maintained 50 mass% including 0.5 mass% of MWCNT. In order to achieve homogeneous dispersion ball milling process was employed to incorporate the MWCNT into phenolic resin (powder). Thermal results from thermogravimetric analysis and differential scanning calorimetric analysis revealed that the hybrid composites (35/15; 35 mass% CR and 15 mass% K) showed higher thermal stability among the composite samples. Visco-elastic results revealed that kenaf fiber-based MWCNT-modified composites (0/50; 0 mass% CR and 50 mass% K) exhibited higher storage and loss modulus due to high modulus kenaf fiber. Fire-retardant analysis (UL-94) showed that all the composite samples met H-B self-extinguishing rating and exhibited slow burning rate according to limiting oxygen index (LOI) test. However, (15/35; 15 mass% CR and 35 mass% K) hybrid composites showed the highest time to ignition, highest fire performance index, lowest total heat release rate, average mass loss rate, average fire growth rate index and maximum average rate of heat emission. Moreover, the smoke density of all hybrid composites was found to be less than 200 which meets the federal aviation regulations (FAR) 25.853d standard. Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) was carried out to select an optimal composite sample considering the thermal, visco-elastic and fire-retardant behaviors. Through TOPSIS analysis, the hybrid (15/35; 15 mass% CR and 35 mass% K) composite sample has been selected as an optimal composite which can be used for high-temperature aircraft and automotive applications.